2020
DOI: 10.1088/1361-6668/abad86
|View full text |Cite
|
Sign up to set email alerts
|

Rules of non-superconducting phase particles on crack propagation in YBCO coated conductors fabricated by the IBAD-MOCVD

Abstract: Cracks caused by tensile stress in YBa2Cu3O7-x-coated conductors (YBCO-CCs) can cause irreversible degradation to their superconducting properties. Understanding the initiation and propagation modes of cracks can assist in preventing conductor failure and enhancing their mechanical properties in further. In this study, we used a chemical etching method and scanning electron microscopy to investigate crack morphology in the YBCO layer of conductors where the protective metal layer had been removed. For YBCO-CCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The slits or cracks caused by manufacturing process can weaken the delamination strength. And the experimental results show that the delamination can cause the cracks in the REBCO layer of CC [59], and the appearance of cracks in the REBCO layer may be one of the major reasons for the performance degradation. Based on the above conclusions, we assume that the performance degradation of coils can be positively associated with the extent of delamination in the coils and the number of cracks in the REBCO layer.…”
Section: Effects Of Electromagnetic Forces and Initial Localized Dama...mentioning
confidence: 99%
“…The slits or cracks caused by manufacturing process can weaken the delamination strength. And the experimental results show that the delamination can cause the cracks in the REBCO layer of CC [59], and the appearance of cracks in the REBCO layer may be one of the major reasons for the performance degradation. Based on the above conclusions, we assume that the performance degradation of coils can be positively associated with the extent of delamination in the coils and the number of cracks in the REBCO layer.…”
Section: Effects Of Electromagnetic Forces and Initial Localized Dama...mentioning
confidence: 99%
“…One of the most serious technical problems is the degradation of REBCO performance observed after tape cabling, or during the winding of a magnet or in its operation. In these circumstances, mechanical loads often cause irreversible damage to the brittle REBCO layer [15][16][17][18]. Defects in the REBCO layer lead to critical current reduction and consequently to a decrease in the current transmission capacity of the cable.…”
Section: Introductionmentioning
confidence: 99%
“…As the GdBCO superconducting film is located close to the neutral axis, it is better to be used in winding [20]. Zhang et al [24,25] found that with the increase in tensile strain, cracks first appeared in the YBCO layer on the side close to the buffer layer firstly and then expanded to the side close to the silver layer, pointing out the potential direction for improving the CC tension tolerance by improving the elastic properties or changing the elastic states of substrates of CCs.…”
Section: Introductionmentioning
confidence: 99%